The effects of water flow rate on copper corrosion - Mahmood, Mahmood Hameed; -, Suryanto; Al Hazza, Muataz Hazza Faizi (Trans Tech Publications, 2017)
This study investigates the effect of water flowrate on the copper alloy corrosion by using a hydrodynamic corrosion test in operating conditions of water flow rate range between 0.05 and 3.5 m/s, the temperature range between 20 and 45 °C. Dissolved oxygen concentration was in the range between 6.1 and 9.2 mg/l. The effects of water properties density, viscosity, and the tube geometric dimensions also considered. Corrosion rate determined by the weight loss calculation method and the tested samples microstructures characterized using FESEM. The results showed that the copper surface layer more affected by water flow at the beginning of turbulent flow condition, while at fully developed turbulent flow condition the surface covered with a fixed oxide layer. Therefore, corrosion found to be at higher rates during the initial stage of the turbulent flow condition, but it reduced at fully developed turbulent flow conditions at higher water velocity. These results indicate that the overall flow rate conditions, which include physical properties of the fluid, hydrodynamic parameters, and the geometric tube dimensions, have the dominant influence on corrosion rate.